Investigations into the application of a combination of bioventing and biotrickling filter technologies for soil decontamination processes — A transition regime between bioventing and soil vapour extraction - Magalhães, S.M.C. (2010)
Bioventing has emerged as one of the most cost-effective in situ technologies available to address petroleum light-hydrocarbon spills, one of the mostcommonsources of soil pollution. However, themajor drawback associated with this technology is the extended treatment time often required. The present study aimed to illustrate how an intended air-injection bioventing technology can be transformed into a soil vapour extraction effort when the air flow rates are pushed to a stripping mode, thus leading to the treatment of the off-gas resulting fromvolatilisation. As such, a combination of an air-injection bioventing system and a biotrickling filter was applied for the treatment of contaminated soil, the latter aiming at the treatment of the emissions resulting from the bioventing process. With a moisture content of 10%, soil contaminated with toluene at two different concentrations, namely 2 and 14mgg soil−1, were treated successfully using an air-injection bioventing system at a constant air flow rate of ca. 0.13dm3 min−1, which led to the removal of ca. 99% toluene, after a period of ca. 5 days of treatment. A biotrickling filter was simultaneously used to treat the outlet gas emissions, which presented average removal efficiencies of ca. 86%. The proposed combination of biotechnologies proved to be an efficient solution for the decontamination process, when an excessive air flow rate was applied, reducing both the soil contamination and the outlet gas emissions, whilst being able to reduce the treatment time required by bioventing only.